Determinação de cádmio e chumbo em sangue por espectrometria de absorção atômica com tubo aquecido na chama após combustão iniciada por microondas - Hoehne, Lucélia (2007)
In this work a procedure for Cd and Pb determination by solid sampling flame furnace atomic absorption spectrometry after microwave induced combustion (MIC-FF-AAS) is used. Human blood samples were priory lyophilized, dried, ground, mixture with graphite, pressed and placed on a filter paper positioned on a quartz holder, that was introduced in a glass device inside a microwave oven. The microwave oven was modified making possible an oxygen flow for combustion step and to transport the combustion products to the AAS spectrometer. Ammonium nitrate solution 50% (w/v) was used to start the ignition step. Atomization was performed in a metallic tube heated into air and acetylene flame. Calibration was carried out using aqueous reference solutions pipetted into graphite pellets. After operational conditions optimization, the suitable parameters were: 20 mg of paper filter to start combustion with 40 μl of NH4NO3 50% (w/v), 1 l min-1 O2 flow rate and air and acetylene flow rates were 16 and 2 l min-1 for determination of Cd and Pb in lyophilized blood using tubes without for Cd and with 12 holes for Pb. At the chosen conditions it was possible the introduction of around 50 mg of sample and quantification limits of 20 ng g-1 and 2.2 μg g-1, for Cd and Pb, respectively. The obtained characteristic masses were 50 pg for Cd and 4.5 ng for Pb. No significant differences were observed when comparing the obtained results using the proposed procedure with certified reference materials values or with those obtained by inductively coupled plasma mass spectrometry, after acid digestion. The sample throughput was 15 determinations per hour, excluding previous steps until weighing step.